Overtime Work as a Signaling Device - Silke Anger (Scottish Journal of Political Economy, 2008)
This paper provides an explanation for the empirically proven relationship between overtime and future benefits. We suggest an internal signaling model, in which a worker signals his value to the employer by supplying unpaid overtime. In our empirical analysis, we examine whether overtime has in fact a signaling component. Variations in collectively bargained hours between industries are exploited, as they imply different overtime thresholds for workers with the same number of actual hours. Using data from the German Socio-Economic Panel Study for the years 1993–2004, a positive signaling value of unpaid overtime is found for West German workers.
Additional information: The definitive version is available at onlinelibrary.wiley.com: http://dx.doi.org/10.1111/j.1467-9485.2008.00449.x
Keywords: J22; D82; J41; 330; Unpaid Overtime; Internal Signaling; Asymmetric Information; Arbeit; Arbeitszeit; Lohn; Alte Bundesländer